Ubiquitin specific peptidases and prostate cancer - Guo, Yunfei; Cui, Shuaishuai; Chen, Yuanyuan; Guo, Song; Chen, Dahu (PeerJ, 2023)
Protein ubiquitination is an important post-translational modification mechanism, which regulates protein stability and activity. The ubiquitination of proteins can be reversed by deubiquitinating enzymes (DUBs). Ubiquitin-specific proteases (USPs), the largest DUB subfamily, can regulate cellular functions by removing ubiquitin(s) from the target proteins. Prostate cancer (PCa) is the second leading type of cancer and the most common cause of cancer-related deaths in men worldwide. Numerous studies have demonstrated that the development of PCa is highly correlated with USPs. The expression of USPs is either high or low in PCa cells, thereby regulating the downstream signaling pathways and causing the development or suppression of PCa. This review summarized the functional roles of USPs in the development PCa and explored their potential applications as therapeutic targets for PCa.
Keywords: Ubiquitin-specific proteases (USPs); Deubiquitination; Prostate cancer